Implementasi Program KPR Syariah Bersubsidi terhadap Masyarakat Berpenghasilan Rendah di Bank Tabungan Negara (BTN) Kota Langsa Aceh - Faisal Umardani Hasibuan (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This research is entitled “Effectiveness of Subsidized Sharia Mortgage Financing for Low- Income Communities at BTN Syariah Langsa City. This study uses a qualitative descriptive method, with the formulation of the problem, 1) How is the implementation of Islamic mortgage financing for low-income customers at Bank BTN Langsa City?, 2) How is the effectiveness of Islamic mortgage financing for low-income people at Bank BTN Langsa City?, from the results of the research of the bank and the dispatcher have followed the regulations from the government from the housing mortgage program, but with regulations from the government, the depeloper is an obstacle they cannot freely choose customers, with regulations made by the government even though people who are gardeners are farmers and fishermen even though they are able to take mortgage housing, there are also people who feel helped by the KPR program from thegovernment.